Maudu Lompoa: A Tradition to Welcome The Birth of The Prophet Muhammad Saw - Juliyati, Dewi; Rahman, Abdul (International Journal of Social Service and Research, 2021)
This study has a purpose, namely to find out the background of the celebration Maudu Lompoa as the biggest birthday celebration in Cikoang Village, Takalar Regency, to find out how the views of the people in Cikoang Village about the celebration tradition Maudu Lompoa in Cikoang, Takalar Regency, to find out the emergence of the celebration Maudu Lompoa for community in Cikoang, Takalar Regency. This study uses historical research methods consisting of four stages, namely: heuristics (collection of data or sources), source criticism consisting of internal and external criticism, interpretation or interpretation of sources and historiography, namely historical writing. Based on the results of the study, it shows that the Maulid celebration is carried out with the intention of commemorating the Birthday of the Prophet Muhammad SAW which coincides with the 12th of Rabi'ul Awal, where the Maudu Lompoa ceremony is a tradition that has been taught by Sheikh Djalaluddin who is a cleric from Aceh who comes from the descendants of the Prophet Muhammad SAW. Those who come to Cikoang Village aim to preach Islam. The survival of the commemoration of the Prophet's birthday is due to encouragement in the form of religious motivation and social motivation, which are two factors that encourage the people of Cikoang Village to continue to preserve the tradition Maudu Lompoa, so that it has an impact on the community. community, which is seen in the field of social, economic and cultural tourism